An Ethical Study of Antioxidant Property of Snail “Achatina Fulica” via Heat Sonication Method for Moisturizing Lotion Stick - Mufid, Haziq; Aliff Hisyam A Razak,; ’Aisyah Mohamed Rehan, (Progress in Engineering Application and Technology, 2024)
This study investigates the extraction and characterization of mucin from Achatina fulica for its potential use in cosmeceutical lotion sticks. The research aims to address the problem of dried skin during sunny days and the unethical practices in snail mucin extraction, which often fail to meet quality and safety standards. By employing heat and sonication methods within ethical guidelines, the study seeks to optimize mucin extraction. An optimization method generated by the Response Surface Methodology (RSM) was used to identify key factors such as temperature, light intensity, and extraction duration that influence mucin quality and yield. The optimized conditions were found to be 30°C, 410 light intensity, and 20 minutes extraction time. The extracted mucin was yellowish, had a pH of 6.48, was water-soluble, and had nanosized particles (approximately 28.99 d.nm). Chemical analysis revealed the presence of Hyaluronic Acid, a key moisturizing agent. Biological testing of the lotion stick formulated with snail mucin and virgin coconut oil demonstrated enhanced moisturizing properties and antioxidant ability with increased mucin concentration. Additionally, the mucin exhibited significant antibacterial activity, inhibiting E. coli (11mm inhibition zone) and S epidermidis (7mm inhibition zone). This research contributes to the field of cosmeceuticals by providing valuable insights into the ethical extraction and potential benefits of Achatina fulica mucin. The findings support its use as a trending ingredient in skincare products, emphasizing both efficacy and ethical considerations in extraction practices.